Central limiting theorem for nonuniform processes with independent increments with semi-Markovian change overs - Korolyuk , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
The central limit theorem for nonhomogeneous processes with independent increments with semi-Markov switchings with a uniformly ergodic imbedded Markov chain is proved.